The Research Bulletin 2016 - Ab Rahman, Ismail (Pusat Pengajian Sains Pergigian, 2016)
It is my great pleasure and privilege to bring greetings to you from the School of Dental Sciences, USM. This school began in 1998 with a simple but profound mission of becoming a centre of excellence in academia, innovation and research, as well as services and be the catalyst and leader for new knowledge in teaching, learning, research and services for Malaysian higher education and the world. As more research grants were awarded, it is high time to expect more publications, patents and products to be produced by researchers. The value of publications could be measured by its impact factor and its placing in the quartiles, as issued by the Thomson-Reuters' Web of Science. The value of one article can also be regarded from the citation it accumulates over the years, as evident in the Scopus database. However, the impact of research should not only be measured by the number of publications produced, but also by virtue of its significance to the society and country if not the world. Apart from that, it is equally important to share the knowledge by disseminating it to the public through conferences, seminars or workshops, which is attended by peers and professionals with similar research interest. In this inaugural issue, we would like to thank Prof. Dr. Ismail Ab Rahman for sharing his life story with us. We believe his success story could be a morale booster to all of us, fellow researchers. I also would like to thank the committee members and all contributors to this project. Let us all strive for a better future.